Humidity-Sensitive PMMA Fiber Bragg Grating Sensor Probe for Soil Temperature and Moisture Measurement Based on Its Intrinsic Water Affinity - Heng Wang (MDPI AG, 2021)
Soil moisture measurement is very important for soil system monitoring. Compared to the traditional thermo-gravimetric technique, which is time-consuming and can be only performed in labs, the optic-fiber technique has unique advantages, such as small size, remote application in fields, fast response time and immunity to electromagnetic fields. In this paper, the soil moisture is measured by using a polymer optical fiber Bragg grating (POFBG) probe with a packaged dimension of 40 mm × 15 mm × 8 mm. Due to the intrinsic water-absorbing property of poly (methyl methacrylate) (PMMA), optical fiber Bragg gratings based on PMMA have been widely investigated for humidity measurement. Taking advantage of this, a sensor based on the POFBG is investigated to verify the soil condition. The POFBG is protectively integrated inside a stainless-steel package. A window is opened with a thin polypropylene mat as a filter, which allows the air to go through but prevents the soil from going inside to pollute the POFBG. The sensor probe is embedded in soils with different gravimetric soil moisture contents (SMCs) ranging from 0% to 40% and, then, insulated by polyethylene films to minimize the impact from the external environment, showing an average temperature cross sensitivity of −0.080 nm/°C. For a constant temperature, an exponential relationship between the Bragg wavelength and the SMC is obtained. For the SMCs between 8% and 24%, linear relationships are presented showing a temperature-corresponded sensitivity between 0.011 nm/% and 0.018 nm/%. The maximal sensitivity is calculated to be 0.018 nm/% at 20 °C, which is 28 times as high as that in the previous work. For the SMC over 24%, the sensor becomes insensitive because of humidity saturation in the cavity of the sensor probe. Though temperature cross sensitivity is problematic for SMC measurement, the influence could be eliminated by integrating another humidity-insensitive temperature sensor, such as a silica FBG temperature sensor.